Вплив температури на оптичні властивості тонких плівок Cu2ZnSnSe4 - Maystruk, E. V.; Koziarskyi, I. P.; Koziarskyi, D. P.; Maryanchuk, P. D. (PE "Politekhperiodika", Book and Journal Publishers, 2018)
The use of solar cells in various fields of science and technology contributes to the development of materials science and scientific activity in this area. Recently, scientists have been researching the optical and electrical properties of materials such as casterite. Casterite is a natural mineral which consists mainly of copper, zinc, tin, sulfur and selenium, that is, elements that are fairly widespread in nature. Therefore, solar cells, developed on the basis of casterite, will have, according to the researchers, a low cost. In addition, casterites belong to direct-gap semiconductors with a band gap of 0.9—1.5 eV and with a large optical absorption coefficient (≈ 104cm-1).In this work, the authors investigate the effect of temperature on the optical properties of Cu2ZnSnSe4 thin films of casterite obtained by the method of RF magnetron sputtering of previously synthesized material on glass substrates. Optical coefficients were determined by a method based on independent measurement of reflection and transmission coefficients. The reflection coefficient was studied at room temperature, and the transmittance — in the temperature range of 111—290 K. The measurements were made in the wavelength range from 0.9 to 26 μm. The obtained data were used to calculate the absorption coefficient and the band gap of the samples at different temperatures from the range under study. Studies have shown that direct interband optical transitions are observed in Cu2ZnSnSe4 films. The optical band gap at room temperature was 0.92 eV at a temperature coefficient of -1,29·10–4 eV/K, that is, the optical band gap decreases with temperature, which is typical of classical semiconductors.